2010
DOI: 10.1089/jop.2010.0060
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Preservative-Free Eye Drops Containing a Fixed Combination of Dorzolamide and Timolol in Glaucoma Patients

Abstract: This observational study confirms the IOP lowering effect of preservative-free eye drops containing the fixed combination of dorzolamide/timolol in a large patient's population. The drug was well tolerated and improved the local tolerability in the vast majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The present study observed that latanoprost was associated with maximum number of ADRs to 9 patients (18 %) (Iris pigmentation to 3 patients (6 %)), conjunctival hyperemia to 5 patients (10 %), hypertrichosis to 1 patient (2 %) followed by acetazolamide to 7 patients (14 %) (Numbness in both hands 4 patients (8 %)), gastritis with bitter taste in mouth 3 patients (6 %), then dorzolamide (eye redness) 4 patients (8 %), then timolol 3 patients (6 %) (drowsiness 2 patients (4 %)), allergic conjunctivitis 1 patient (2 %), and pilocarpine (headache) 2 patients (4 %). Comparing our study to one in Germany, which were quite similar [24], out of 2 298 glaucoma patients requiring intraocular pressure (IOP) reduction, and patients were treated with anti glaucoma medication for 12 weeks. Main efficacy endpoint was IOP reduction after 12 weeks of treatment.…”
Section: Discussion ▼mentioning
confidence: 80%
“…The present study observed that latanoprost was associated with maximum number of ADRs to 9 patients (18 %) (Iris pigmentation to 3 patients (6 %)), conjunctival hyperemia to 5 patients (10 %), hypertrichosis to 1 patient (2 %) followed by acetazolamide to 7 patients (14 %) (Numbness in both hands 4 patients (8 %)), gastritis with bitter taste in mouth 3 patients (6 %), then dorzolamide (eye redness) 4 patients (8 %), then timolol 3 patients (6 %) (drowsiness 2 patients (4 %)), allergic conjunctivitis 1 patient (2 %), and pilocarpine (headache) 2 patients (4 %). Comparing our study to one in Germany, which were quite similar [24], out of 2 298 glaucoma patients requiring intraocular pressure (IOP) reduction, and patients were treated with anti glaucoma medication for 12 weeks. Main efficacy endpoint was IOP reduction after 12 weeks of treatment.…”
Section: Discussion ▼mentioning
confidence: 80%
“…30 Renieri et al noted that preservative-free DTFC was well tolerated and improved the local tolerability in glaucoma patients. 31 Shedden et al compared the efficacy and tolerability of preservative-free and preservative-containing formulations of DTFC in patients with elevated IOP and noted that both combinations were equivalent in efficacy for change in trough and peak IOP, and generally had similar tolerability. 32 In conclusion, LTFC and DTFC are effective in lowering IOP and well-tolerated FCs for patients with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Rolle et al 19 showed that timogel preservative-free dosed once every morning had a 24-h hypotensive effect with a better safety profile than timolol 0.5% twice daily. Efficacy and tolerability of preservative-free eye drops containing a fixed combination of dorzolamide and timolol in glaucoma patients were evaluated in a prospective, multicentre study 20. This study confirmed the IOP-lowering effect of preservative-free fixed combination of dorzolamide–timolol in a large patient population.…”
mentioning
confidence: 60%